Answer:
54565656
Step-by-step explanation:
ggfght
Let's solve your equation step-by-step.<span><span><span><span>2<span>x2</span></span>−<span>3x</span></span>−4</span>=0</span>Step 1: Use quadratic formula with a=2, b=-3, c=-4.<span>x=<span><span><span>−b</span>±<span>√<span><span>b2</span>−<span><span>4a</span>c</span></span></span></span><span>2a</span></span></span><span>x=<span><span><span>−<span>(<span>−3</span>)</span></span>±<span>√<span><span><span>(<span>−3</span>)</span>2</span>−<span><span>4<span>(2)</span></span><span>(<span>−4</span>)</span></span></span></span></span><span>2<span>(2)</span></span></span></span><span>x=<span><span>3±<span>√41</span></span>4</span></span><span><span>x=<span><span>34</span>+<span><span><span><span>14</span><span>√41</span></span><span> or </span></span>x</span></span></span>=<span><span>34</span>+<span><span><span>−1</span>4</span><span>√<span>41</span></span></span></span></span>
Answer:
x=9 and z=83
Step-by-step explanation:
First you subtract 97 from 180 because that gives you z because 180 is a flat angle and 83 plus 97 gives 180. For x the opposite angle is also 97 so you set the equation 5x + 52 = 180 and you solve for x to get the x value. Hope this helps :)
Answer:
B
Step-by-step explanation: